Qualified Empathy: A key element for an empowerment professional - Raatikainen, Eija; Rauhala, Leigh Anne; Mäenpää, Seija (Sosiaalipedagoginen aikakauskirja, 2017)
Studies have shown that when clients experience empathy during their interactions with empowerment professionals, the results of the work are better (Gerdes & Segal 2011). Empathy has also been shown to reduce burnout and protect against secondary traumatic stress in professionals (Wagman, Geiger, Shockley & Segal 2014). This analysis examines and asks what an empowering professional is and what "qualified" empathy is all about? How can it be learned and taught effectively in higher education contexts? In this paper, we will describe how teaching and learning to use empathy has been a part of studies for Social Services students. We argue that professional empathy can be approached in multisensory ways when studying empathy (e.g. Austring & Sørensen 2006). In our case, we have used traditional learning and teaching methods alongside creative methods such as visual arts and drama as ways to learn and teach empathy. Social pedagogically speaking, professional empathy is not just seen as a 'tool' or 'thinking framework' in encountering clients, increasing empowerment, or supporting the process of inclusion, but it can also be seen as one of the core competencies for students (as future professionals). It also has an important role in their professional growth and activities. This paper presents results of the project called "Qualified Empathy" (2015-2017, NORDPLUS). The project took place in the Helsinki Metropolia University of Applied Sciences, as well as in Norway and Denmark as a way to develop diverse and creative teaching and learning methods to help Social Services students (N=47) to learn and develop more professional empathy skills as part of the course. As a part of this review, we have paid attention to individual descriptions as well as to pedagogical perspectives on how empathy can be learned and taught in higher education. We will also consider what needs to be addressed in the teaching and learning contexts in the future. The text combines a social pedagogical approach to the learning and teaching of empathy. *** Tutkimuksin on osoitettu, että työn tulokset ovat parempia, jos asiakkaat saavat kokea empatiaa vuorovaikutuksessaan ammattilaisten kanssa (Gerdes & Segal 2011). Toisaalta empatian on todettu vähentävän myös työntekijöiden loppuun palamista (Wagman, Geiger, Shockley & Segal 2014). Tässä katsauksessa tarkastellaan ammatillista empatiaa ja sen oppimista ja opettamista korkeakoulukontekstissa. Kysymme tässä tekstissä, mitä ammatillinen empatia on ja miten sitä voidaan oppia ja opettaa korkeakoulukontekstissa. Ammatillisella empatialla tarkoitetaan tässä yhteydessä moniaistillista tapaa oppia ja opiskella empatiaa (esim. Austring & Sørensen 2006). Tällöin perinteisten oppimis- ja opetusmenetelmien rinnalla myös luovat menetelmät kuten kuvataide ja draama ovat keskeisiä tapoja oppia ja opettaa empatiaa. Sosiaalipedagogisesti ajateltuna ammatillinen empatia ei ole vain "työväline" tai "ajattelukehikko" asiakkaan kohtaamiseen, voimaannuttamiseen tai osallistamiseen, vaan se voidaan nähdä myös keskeisenä opiskelijan (tulevan ammattilaisen) ammatillisen kasvun ja ammatillisen toiminnan ytimenä, sosiaalipedagogisena sydämenä. Tässä katsauksessa esitellään NORPLUS-hankkeen "Qualified Empathy" (2015-2017) aikana Metropolia Ammattikorkeakoulussa ja sen kumppanikorkeakouluissa kehitettyjä monimuotoisia ja luovia opetus- ja oppimismenetelmiä, joiden avulla sosionomiopiskelijoille (n=47) opetettiin empatiaa osana opintojaksoa. Huomio kiinnittyy yksilöllisten kokemusten lisäksi pedagogiseen näkökulmaan, kuinka empatiaa voidaan oppia ja opettaa ja millaisia asioita siinä yhteydessä tulisi huomioida. Teksti yhdistää sosiaalipedagogisen lähestymistavan empatian oppimiseen ja opettamiseen.